ANALISIS KELAYAKAN FINANSIAL DAN FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENANGKAR DALAM MENGUSAHAKAN BIBIT KARET BERSERTIFIKAT DI KECAMATAN ABUNG SEMULI KABUPATEN LAMPUNG UTARA - Dani Pramaditya Trisnata; R Hanung Ismono; Achdiansyah Soelaiman (Lampung University, 2017)
The purposes of this research are to describe rubber seed certification process, analyze factors influencing breeders in making decision on managing certified rubber seed, and analyze financial feasibility of certified and noncertified rubber seed businesses. This research was conducted in Abung Semuli District, North Lampung Regency. The total of the sample is 32 breeders consisting of 12 breeders who manage certified rubber seed and 20 breeders who manage noncertified rubber seed. The data analysis methods used in this research are descriptive qualitative analysis, logit analysis, and financial advisability analysis. The results showed that breeders who have TRUP should send UPTD BP2MD requirements for certification. Next BP2MD will do physical and administrative investigation, if all requirments was fulfilled the breeders will be given a certificate of quality. Factors which influnce breeders in cerified rubber seed business are level of education, age, price, and income on operating expenses. Financially rubber seed certificate business in Abung Semuli District is more profitable than noncertificate business. Key words : financial feasibility, seed certification, and making decision